Design and Implementation of Modified Partial Product Reduction Tree for High Speed Multiplication - Sachin B. Jadhav; Jayamala K. Patil; Ramesh T. Patil (Institute of Advanced Engineering and Science, 2013)
This paper presents the details of hardware implementation of modified partial product reduction tree using 4:2 and 5:2 compressors. Speed of multiplication operation is improved by using higher compressors .In order to improve the speed of the multiplication process within the computational unit; there is a major bottleneck that is needed to be considered that is the partial products reduction network which is used in the multiplication block. For implementation of this stage require addition of large operands that involve long paths for carry propagation. The proposed architecture is based on binary tree constructed using modified 4:2 and 5:2 compressor circuits. Increasing the speed of operation is achieved by using higher modified compressors in critical path. Our objective of work is, to increase the speed of multiplication operation by minimizing the number of combinational gates using higher n:2 compressors. The experimental test of the proposed modified compressor is done using Spartan-3FPGA device (XC3S400 PQ-208). Using tree architectures for the partial products reduction network represent an attractive solution that is frequently applied to speed up the multiplication process. The simulation result shows 4:2 and 5:2 compressor output which is done using Questa Sim 6.4c Mentor Graphics tool.